"You tell him that 'baby, I am protecting myself'": Women's agency and constraint around willingness to use pre-exposure prophylaxis in the Masibambane Study. (March 2022) - Harrison, Abigail; Bhengu, Nonhlonipho; Miller, Lori; Exner, Theresa; Tesfay, Nonkululeko; Magutshwa, Slindile; Khumalo, Silindile; Bergam, Scarlett; Hoffman, Susie; Hanass-Hancock, Jill
Objectives: To explore women's willingness to consider using pre-exposure prophylaxis for HIV prevention in the context of gendered relationship dynamics, in Durban, South Africa. Methods: As formative research prior to development of a gender-informed intervention to introduce pre-exposure prophylaxis to young, urban, educated women, we conducted six focus-group discussions and eight in-depth interviews with 46 women ages 18–25 years, who were not current pre-exposure prophylaxis users. Women were recruited from clinic and community settings using a criterion-based snowball sampling technique. Qualitative data were coded and analyzed thematically, with a team-based consensus approach for final coding, analytical decisions, and data interpretation. Results: Women clearly understood the benefits of pre-exposure prophylaxis for themselves and their partners, focusing on promoting health and their right to protect themselves from HIV infection. At the same time, and in accordance with findings from other studies, women were realistic about the concerns that would arise among male partners, including disapproval, loss of trust, possible loss of the relationship, and in some instances, the potential for violence, if they were to propose pre-exposure prophylaxis use. To resolve this tension, some women advocated for covert use as the best option for themselves and others argued for disclosure, proposing various approaches to working with partners to adopt pre-exposure prophylaxis. The suggestion that both partners use pre-exposure prophylaxis was made repeatedly. Thus, women sought to avoid discussions of trust or lack of trust and a partner's possible infidelities, choosing instead to focus on preserving or even building a relationship through suggesting pre-exposure prophylaxis use. Conclusion: Women offered diverse narratives on agency and constraint in relation to choosing pre-exposure prophylaxis as a future prevention strategy, as well as ways to engage with their male partners about pre-exposure prophylaxis. These findings speak to the need for interventions to bolster women's confidence, sense of empowerment, and their communication and decision-making skills for successful HIV prevention.